Analysis and Water Quality Control of Alternative Sources in Bangolan, Northwest Cameroon - Nchofua Festus Biosengazeh; Njoyim Estella Buleng Tamungang; Mofor Nelson Alakeh; Mvondo-ze Antoine david (Journal of Chemistry)
This research focused on the quality of domestic water in Bangolan, Northwest Cameroon, in order to ascertain its potability based on World Health Organisation (WHO) guidelines. Inhabitants of this locality, as well as others in rural areas, consume water from these sources without any prior treatment which can lead to contamination and infections. Sampling was conducted, and physicochemical and bacteriological properties of ten water sources were examined in November 2017 and January, April, and July 2018 using standard methods. The results showed that the sampled water sources were moderately acidic to weakly basic falling within the WHO specification. The values of electrical conductivity and total dissolved solids were low, suggesting low mineralised waters which could lead to a shortage of essential mineral elements in humans. Water turbidity was high in July, attributable to the rains. Major ions analysed fell within the WHO guideline values except iron and aluminium, whose values fell above guideline values in both seasons due to the nature of the soils. Faecal coliforms were found in all the sources, and specific bacteria identified were Escherichia coli, Enterobacteria, Streptococcus, Salmonella, and Shigella spp., suggesting recent contamination by faecal matter due to poor hygienic conditions, and hence, treatment was recommended. Statistical analyses revealed significant influence of heavy rains on most water parameters (p<0.05). Health data in the locality revealed 1389 cases of water-borne diseases, namely, typhoid, diarrhoea, and dysentery between 2016 and 2017 necessitating control.